Analisis Pengaruh Proactive Personality dan Psychological Capital Terhadap Individual Work Performance yang Dimediasi Oleh Work Engangement Pada Industri Fast Food di Jakarta Pusat - Felisa Salsabila; Netania Emilisa; Sherly Sanchia Stacia Fam; Fitriyah Ningsih (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of Proactive Personality and Psychological Capital on Individual Work Performance with Work Engagement as a mediating variable among fast food employees in Central Jakarta, who have fast-paced work characteristics and high turnover rates, thus requiring employees to have psychological factors and proactive behaviors in order to maintain optimal performance. The research was designed using a hypothesis testing approach with a descriptive quantitative method and purposive sampling technique. Data were collected through an online questionnaire administered to 160 respondents and measured using a 5-point Likert scale. The data analysis method used descriptive statistics with SPSS, testing the influence using Structural Equation Modeling (SEM) with AMOS, testing the mediation of Work Engagement with the Sobel test, and evaluating the model fit theory. The results showed that Proactive Personality, Psychological Capital, and Work Engagement had a significant effect on Individual Work Performance among fast food employees in central Jakarta. Furthermore, Proactive Personality and Psychological Capital significantly influence Work Engagement, while the mediation analysis shows that Work Engagement does not significantly influence the relationship between Proactive Personality and Psychological Capital on Individual Work Performance. The implications of this study are that companies should focus on strengthening employees' personality and psychological factors and creating a work environment that supports dedication and enthusiasm to improve individual performance.